2009
DOI: 10.1002/adfm.200801767
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Iridium(III) Complexes with Bulky Side Groups for Use in Light Emitting Cells: Reduction of Concentration Quenching

Abstract: Here, the photophysics and performance of single‐layer light emitting cells (LECs) based on a series of ionic cyclometalated Ir(III) complexes of formulae $\left[ {{\rm Ir}\left( {{\rm ppy}} \right)_{\rm 2} \left( {{\rm bpy}} \right)} \right]^ + {\rm PF}_{\rm 6}^ -$ and $\left[ {{\rm Ir}\left( {{\rm ppy}} \right)_{\rm 2} \left( {{\rm phen}} \right)} \right]^ + {\rm PF}_{\rm 6}^ -$ where ppy, bpy, and phen are 2‐phenylpyridine, substituted bipyridine and substituted phenanthroline ligands, respectively, are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 39 publications
5
124
0
3
Order By: Relevance
“…The photophysical, electrochemical, and theoretical studies showed that addition of the bulky groups does not affect the emitting excited state, in agreement with other reports. [182,183] LECs using these complexes exhibit a roughly sixfold increase in the EQE when compared with the archetype complex without phenyl and phenolic ether groups. Additionally, other important device parameters, such as turn-on time, luminance, and stability improved upon increasing the size of the bulky groups.…”
Section: Using Bulky Groupsmentioning
confidence: 96%
See 1 more Smart Citation
“…The photophysical, electrochemical, and theoretical studies showed that addition of the bulky groups does not affect the emitting excited state, in agreement with other reports. [182,183] LECs using these complexes exhibit a roughly sixfold increase in the EQE when compared with the archetype complex without phenyl and phenolic ether groups. Additionally, other important device parameters, such as turn-on time, luminance, and stability improved upon increasing the size of the bulky groups.…”
Section: Using Bulky Groupsmentioning
confidence: 96%
“…[182,183] The addition of bulky groups and high luminances (1000 cd m À2 at 3 V). Notably, there are limits in the use of large substituents because driving voltages tend to increase as a consequence of larger intermolecular separation.…”
Section: Using Bulky Groupsmentioning
confidence: 99%
“…23,29 However, bulky groups are known to slow down the migration of the ions in the device inducing long turn-on times. 30,31 Hence, there is still room to explore new strategies and ligands in search for higher performances and stabilities. In this work, we introduce a series of new complexes with arylazole-based ancillary ligands without bulky groups, and use them to prepare LEC devices trying to reach high stabilities without affecting the turn-on times.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, time resolved spectra from both the exponential part and the power law part of the curve are exactly the same. This means that emission is coming from the dopant at all times; however, it is unlikely that the power law emission is coming from excitons formed as a result of recombination on the dopant due to the short radiative lifetime of the dopant (in the range of 1 to 2 µs, [10,11,15] whereas the power law feature lasts up to milliseconds). We can also discount the hypothesis that the dopant, at late times, is fed from either PBD or PVK triplet states, as it is very unlikely that triplets formed on the PVK and PBD molecules have a lifetime in the range of milliseconds at room temperature ( Figure 4).…”
Section: 2 Iridium(iii)bis[2-(24-difluorophenyl)-4-(246-trimethymentioning
confidence: 99%